Optimization of mechanical properties of electrospun epoxidized natural rubber/ acrylonitrile-butadiene-styrene (ENR/ABS) fibre for membrane application - Mahathir Mohamed,; Abu Bakar Sulong,; Rosiah Rohani,; Mohammed Iqbal Shueb,; Mohd Sofian Alias,; Mohd Hamzah Harun, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study created membrane nanofibres using the electrospinning method and newly studied a mixture of ENR and ABS. The two-level complete factorial designs with centre points were used to characterise the functionality of the constructed membrane. The variables considered for experimental design were the polymer concentration, materials ratio (ENR concentration), applied voltage and distance between the needle tip and collector. According to the analysis of variance (ANOVA), the concentration of solution and distance were statistically significant parameters that affected the tensile properties of the ENR/ABS electrospun membrane. A mathematical model of the tensile property of polymer fibres was created using Response Surface Methodology (RSM). This model was built based on essential process factors. The mechanical properties of the electrospun ENR/ABS membrane compromised with 25wt% of solution concentration, 30% ratio of ENR, the voltage at 22.5kV and 15 cm of distance create an excellent tensile strength with desirability of 0.94. The influence of ENR on the morphology of ENR/ABS fibres was characterised by Scanning Electron Microscopy (SEM). The result showed beaded fibre and decreased fibres due to the low concentration of the solution and high ratio of ENR (50%). The contact angle measurements indicated that the electrospun fibre membrane was hydrophobic with a water contact angle of 136°. The addition of ENR showed a reduction in contact angle to 119°. The existence of ENR will change the features of the membrane, and investigations have demonstrated that RSM has been efficiently developed to acquire the interaction effects of processing parameters.